2022
DOI: 10.3390/ph15080962
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction between Atorvastatin and Omega-3 Fatty Acid in Healthy Volunteers

Abstract: The interaction between statins and omega-3 fatty acids remains controversial. The aim of this phase 1 trial was to evaluate the pharmacokinetics of drug-drug interaction between atorvastatin and omega-3 fatty acids. Treatments were once-daily oral administrations of omega-3 (4 g), atorvastatin (40 mg), and both for 14 days, 7 days, and 14 days, respectively, with washout periods. The concentrations of atorvastatin, 2-OH-atorvastatin, docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA) were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As a result, ω-3 fatty acid absorption was increased much more as compared to the commercialized cap Omacor ® . An investigation of the metabolic fate of EPA and DHA revealed that DHA metabolism remained substantially unchanged following stomach oxidation, enhancing DHA bioavailability in comparison to EPA [4,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, ω-3 fatty acid absorption was increased much more as compared to the commercialized cap Omacor ® . An investigation of the metabolic fate of EPA and DHA revealed that DHA metabolism remained substantially unchanged following stomach oxidation, enhancing DHA bioavailability in comparison to EPA [4,21].…”
Section: Discussionmentioning
confidence: 99%
“…In the age of modern medication, high-intensity statins are often recommended as a first-line treatment for hyperlipidemia in reducing LDL-C levels. These statins are potent cholesterol-lowering drugs that have demonstrated effectiveness in lowering LDL-C levels and reducing the risk of cardiovascular incidents [4]. However, it is essential to acknowledge that statins also come with potential risks and side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Atorvastatin trough concentrations (therapeutic range for trough 1.0 ± 0.7 ng/mL after a dose of 40 mg) for the active parent drug were obtained 20 weeks after initiation of active atorvastatin treatment [11]. Participants were required to delay their daily atorvastatin dose on this visit until after the blood draw, approximately 24 h after the prior dose, and reported the time of their last atorvastatin dose.…”
Section: Methodsmentioning
confidence: 99%
“…Inc., Korea) was developed to improve compliance and convenience. While the possibility of drug interactions between atorvastatin and omega-3-acid ethyl esters has been reported, 13 the efficacy and safety of ATMEG CombiGel have been confirmed through a Phase 3 study. 14 The FDC formulation of atorvastatin and omega-3-acid ethyl esters contains atorvastatin tablet inside the omega-3-acid ethyl esters capsule.…”
Section: Introductionmentioning
confidence: 96%